Description of respiratory syncytial virus genotypes circulating in Colombia - Avila, Viviana; Calvo, Eliana; Barbosa, Juliana; Velandia-Romero, Myriam L; Castellanos, Jaime E. (The Journal of Infection in Developing Countries, 2018)
Introduction: Respiratory syncytial virus (RSV) is the most common cause of acute respiratory infections in children younger than two years but also produces infection in older children and even reinfection in people of any age, a characteristic related to the existence of different infecting subtypes and genotypes. Although Colombia has established the surveillance of classical respiratory viruses, there is no information about the RSV genotypes circulating in Colombian patients. Methodology: A subgroup of 227 previously RSV positive respiratory secretion samples were taken from a nationwide surveillance study, amplified and sequenced to define the circulation pattern of RSV subtypes and genotypes during 2000-2009 period in Colombia. Results. RSV exhibited seasonal behavior with an A subtype more prevalent. Both RSV subtypes had low nucleotide variability. During the study period, the GA2 and GA5 genotypes from RSV subtype A and the BA genotype from RSV subtype B were found. Conclusion. In this report, for the first time RSV genotypes circulating in Colombia were described, this information adds valuable information about virus epidemiology helping to understand the RSV epidemic and prepare our country for the introduction of new vaccines.